2014
DOI: 10.1039/c4ob00761a
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine modification by acrolein exclusively produces 1,5-diazacyclooctanes: a previously unrecognized mechanism for acrolein-mediated oxidative stress

Abstract: Acrolein, a toxic unsaturated aldehyde generated as a result of oxidative stress, readily reacts with a variety of nucleophilic biomolecules. Polyamines, which produced acrolein in the presence of amine oxidase, were then found to react with acrolein to produce 1,5-diazacyclooctane, a previously unrecognized but significant downstream product of oxidative stress. Although diazacyclooctane formation effectively neutralized acrolein toxicity, the diazacyclooctane hydrogel produced through a sequential diazacyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…40 Our studies strongly suggested that the 2,6,9-triazabicyclononanes and 1,5-diazacyclooctanes, such as 1 and 2, were the exclusive acrolein-amine conjugates; however, we were surprised to find that the production of the 3-formyl-3,4-dehydropiperidine (FDP) conjugates, which are now widely used as biomarkers of the oxidative stress, were nearly undetectable in our hands in these reaction mixtures. [38][39][40] This paper reports further evidence of the facile and quantitative production of 1,5-diazacyclooctanes 3 (Scheme 1c) from biologically relevant amines other than polyamines, that is, sphingosine and noradrenaline, through a hydroxyl-mediated [4+4] cycloaddition mechanism. We examined the stabilities of three eight-membered heterocycles, namely, 2,6,9-triazabicyclononane 1 (derived from an aliphatic amine) and 1,5-diazacyclooctanes 2 and 3 (derived from either polyamine or noradrenaline derivatives).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…40 Our studies strongly suggested that the 2,6,9-triazabicyclononanes and 1,5-diazacyclooctanes, such as 1 and 2, were the exclusive acrolein-amine conjugates; however, we were surprised to find that the production of the 3-formyl-3,4-dehydropiperidine (FDP) conjugates, which are now widely used as biomarkers of the oxidative stress, were nearly undetectable in our hands in these reaction mixtures. [38][39][40] This paper reports further evidence of the facile and quantitative production of 1,5-diazacyclooctanes 3 (Scheme 1c) from biologically relevant amines other than polyamines, that is, sphingosine and noradrenaline, through a hydroxyl-mediated [4+4] cycloaddition mechanism. We examined the stabilities of three eight-membered heterocycles, namely, 2,6,9-triazabicyclononane 1 (derived from an aliphatic amine) and 1,5-diazacyclooctanes 2 and 3 (derived from either polyamine or noradrenaline derivatives).…”
Section: Introductionmentioning
confidence: 88%
“…The 1,5-diazacyclooctane derivatives were found to be the exclusive products, based on the characteristic 1 H NMR spectrum and the high-resolution MS traces. 40,41 The separation and direct analysis of the equilibrium mixtures 4a and 4b were difficult; therefore, the structure was unambiguously determined by reducing the compounds using LiAlH 4 (5, quantitative yield). The reaction proceeded smoothly in an aqueous PBS buffer solution with an efficiency comparable to that observed in organic solvents.…”
Section: Reaction Of Acrolein With Natural Aminoalcoholsmentioning
confidence: 99%
See 2 more Smart Citations
“…22, 23, 24, 25 We demonstrated that these compounds are produced in much higher amounts and efficiency than the oxidative stress marker, FDP, which thus far has only been detected under standard analytical conditions. This likely suggests that acrolein reacts with polyamines to exclusively produce the eight‐membered heterocycles as initial acrolein‐modified intermediates.…”
Section: Methodsmentioning
confidence: 90%